Labor mobility and fiscal policy in a currency union - Angelo Baglioni; Andrea Boitani; Massimo Bordignon (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2014)
Labor mobility is commonly taken as a property of an optimal currency area. But how does that property aect the outcome of fiscal policies? We address this issue with a two country ?two period model, where both asymmetric and symmetric productivity shocks may hit the countries. We show that perfect (costless) labour mobility is not necessarily welfare improving, since it prevents the national fiscal authorities from pursuing indepen- dent policies, opening the way to a coordination problem between them, which is particularly relevant when the two countries dier for their intertemporal preferences. With symmetric shocks, the federal fiscal policy can improve welfare over national policies by playing a coordinating role. With asymmet- ric shocks, the federal fiscal policy allows both countries to reach a higher productive efficiency; to do that, the federal government must be endowed with a federal budget, playing a stronger role than plain coordination between countries.
Keywords: E62; H77; 330; currency union; labor mobility; fiscal policy; federation